The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1038/sj.npp.1300395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol on Hypothalamic–Pituitary–Adrenal System Response to Psychosocial Stress in Sons of Alcohol-Dependent Fathers

Abstract: Familial risk and environmental stress promote the development of alcohol dependence. This study tested two hypotheses: that a family history for alcoholism is associated with (i) a greater stress response and (ii) more effective stress response dampening by alcohol. We studied 29 high-risk subjects with a paternal history of alcoholism (PHA) and 23 family history negative (FHN) controls all aged 18-26 years, who were recruited using a representative sample of the local area population. Psychosocial stress was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 32 publications
8
52
1
2
Order By: Relevance
“…Our findings showing that cortisol responses were higher in Caucasian FHP subjects than in Caucasian FHN subjects are consistent with theories that greater reactivity to stress is associated with greater risks for alcoholism (Higley et al, 1991;Fahlke et al, 2000). To the best of our knowledge, only two studies have specifically examined the relationship of HPA axis hormonal responses to psychological stress with family history of alcoholism (Dai et al, 2002;Zimmermann et al, 2004). Our observations are in agreement with those of Zimmermann et al (2004), who demonstrated that FHP Caucasian males had higher cortisol and ACTH responses to the TSST compared to FHN Caucasian males.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings showing that cortisol responses were higher in Caucasian FHP subjects than in Caucasian FHN subjects are consistent with theories that greater reactivity to stress is associated with greater risks for alcoholism (Higley et al, 1991;Fahlke et al, 2000). To the best of our knowledge, only two studies have specifically examined the relationship of HPA axis hormonal responses to psychological stress with family history of alcoholism (Dai et al, 2002;Zimmermann et al, 2004). Our observations are in agreement with those of Zimmermann et al (2004), who demonstrated that FHP Caucasian males had higher cortisol and ACTH responses to the TSST compared to FHN Caucasian males.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, differences in HPA-axis dynamics as a function of family history of alcoholism have been found by stimulating the HPA axis with the opioid receptor antagonist naloxone (Wand et al, 1998(Wand et al, , 1999a(Wand et al, , b, 2001Hernandez-Avila et al, 2002) and CRH . More recently, hormonal responses to activation of the HPA axis by psychological stressors have been reported to differ in subjects at high and low risk of alcoholism (Dai et al, 2002;Zimmermann et al, 2004). However, results have been contradictory and the nature of these associations remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown that, when exposed to stressful events, humans are more likely to relapse to ethanol and other drugs (Chaplin et al 2010;Fox et al 2005;Kosten et al 1986;Sinha et al 2000). A factor long known to increase the risk for development and maintenance of alcohol use disorders is environmental stress (Zimmermann et al 2004). Environmental stress may produce an exaggerated endocrine response, which is normalized by alcohol, often in conjunction with genetic risk factors for alcoholism (Sinha 2001(Sinha , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Stress produces a cascade of physiological and psychological effects, each with a distinctive time course. In turn, alcohol administration also influences both ACTH and cortisol secretion (Zimmermann et al 2004). Thus, there are bi-directional relationships between alcohol and stress: alcohol influences responses to stress, and stress changes reactions to alcohol, depending on an individual's pattern of response to alcohol (Childs et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation